Source-Reservoir Characteristics and Accumulation of Gas Chimney-Type Gas Hydrates in Qiongdongnan Basin, Northern South China Sea - Fan, Qi; Li, Qingping; Zhou, Shouwei; Li, Lixia; Zhu, Zhenyu; Lv, Xin (Frontiers in Earth Science, 2022)
The Qiongdongnan Basin is an important gas hydrate exploration area in the South China Sea, but the gas hydrate accumulation process is poorly understood. By selecting an Lingshui (LS) target area and using first-hand geochemical data, three-dimensional seismic data, and an independent thermal insulation and pressure maintaining shipborne core analysis system, in this study, comprehensive geological evaluation was carefully conducted around the gas source and reservoir of the gas chimney hydrates, and the accumulation process was investigated. Geochemical data for a total of 47 sets of gas samples revealed that the gas source of the hydrates in the study area was mainly thermogenic gas supplemented by mixed gas. It was predicted that the contribution of the thermogenic gas to the hydrate accumulation was up to 70%. Using the independent shipborne core analysis system, the characteristics of the low-temperature combustible gas hydrates were determined, and the reservoir in the study area was characterized as non-diagenetic to weakly diagenetic, rich in clay and silt (D50 = 15.1–34.1 μm), weakly self-sustaining, and strongly heterogeneous. Based on the differentiated seismic response of the hydrate layer-gas bearing hydrate layer-shallow gas layer at the top of the gas chimney, the accumulation process in the target area was determined to be as follows: remote thermogenic gas transportation, local microbial genetic gas accumulation, episodic dynamic gas chimney reservoir formation, and source-reservoir control. In addition, the exploration ideas of an effective supply from a gas source and a shallow large-scale sand body are emphasized. The results of this study provide an important reference for the trial production of natural gas hydrates in the South China Sea.